Distribution of Tick Haemaphysalis punctata (Acari, Ixodidae) in Ukraine - Akimov, I.A.; Nebogatkin, I.V. (Вестник зоологии, 2012)
The northern boundary of H. punctata range was studied. This boundary of its native range (where this species is common and its mass reproductions are periodically recorded) was found to go through Odesa, Mykolaiv, Kherson, Zaporizhia, Donetsk and Lugansk oblasts. Clarified that the boundary of its temporary range (where this species occurs periodically and is dependent on human factors totally) was clarified to go through Volyn, Rivne, Zhytomyr, Kyiv, Chernihiv and Sumy regions. The range of H. punctata is fully subjected to anthropogenic factors in areas where this species dwelt in historically recent times only, and in ancestral areas of distribution such factors affects only dynamics and indices of abundance. Изучали северную границу ареала H. punctata. Выяснено, что граница коренного (вид обычен и периодически фиксируются массовые размножения) ареала проходит по Одесской, Николаевской, Херсонской, Запорожской, Донецкой и Луганской областях. Уточнено, что граница временного (вид встречается периодически и полностью зависит от антропогенных факторов) ареала этого вида, проходит по Волынской, Ровенской, Житомирской, Киевской, Черниговской и Сумской областях. Ареал H. punctata полностью подчинен антропогенным факторам только на территориях, где этот вид находился в исторически недавнее время, а на исконных участках распространения антропогенные факторы влияют только на величину и динамику индексов обилия.